Screening and Identification of Xylanase Enzyme-Producing Bacteria in Peuyeum Cassava with 16S rRNA Gene Marker method - Fenti Fatmawati; Muhammad Nur Abdillah; Astri Fatmasari; Yuni Dwi Mulyaningsih (Department of Chemistry, Faculty of Sciences and Informatics, Jenderal Achmad Yani University, 2019)
Peuyeum comes from cassava which is an agricultural commodity that is widely grown in Indonesia as a food which is source of carbohydrates. The types of polysaccharides that compose cassava are starch, cellulose and hemicellulose in the form of xylan. Xylanase is a xylanolytic enzyme that can hydrolyze xylan. The bacteria producing xylanase enzyme has been isolated from peuyeum which is thought to affect the fermentation process. Peuyeum contains starch so that it is one of the sources of the amylase enzyme. But there has never been a study of peuyeum's xylanase enzyme screening. The purpose of this study was to isolate xylanase-producing bacteria on peuyeum and identify these bacterial species by analyzing the 16S rRNA gene so that it could become a new source in the search for enzymes. This study consisted of several stages, namely bacterial isolation, xylanase enzyme screening, morphological testing, bacterial DNA isolation, sequencing, bacterial identifikation with the phylogenetic tree method. Xylanase enzyme producing bacteria in peuyeum has been successfully isolated. Based on the results of phylogenetic tree analysis it was found that XF1 bacteria had the closest homology to Bacillus cereus with 99% similarity.